Regulatory B Cells: An Exciting Target for Future Therapeutics in Transplantation - Nouël, Alexandre; Simon, Quentin; Jamin, Christophe; Pers, Jacques-Olivier; Hillion, Sophie (Frontiers in Immunology, 2014)
Transplantation is the preferred treatment for most end-stage solid organ diseases. Despite potent immunosuppressive agents, chronic rejection remains a real problem in transplantation. For many years, the predominant immunological focus of research into transplant rejection has been T cells. The pillar of immunotherapy in clinical practice is T cell-directed, which efficiently prevents acute T cell-mediated allograft rejection. However, the root of late allograft failure is chronic rejection and the humoral arm of the immune response now emerges as an important factor in transplantation. Thus, the potential effects of Abs and B cell infiltrates on transplants have cast B cells as major actors in late graft rejection. Consequently, a number of recent drugs target either B cells or plasma cells. However, immunotherapies, such as the anti-CD20 B cell-depleting Ab, can generate deleterious effects on the transplant, likely due to the deletion of beneficial population. The positive contribution of regulatory B (Breg) cells -or B10 cells- has been reported in the case of transplantation, mainly in mice models and highlights the primordial role that some populations of B cells can play in graft tolerance. Yet, this regulatory aspect remains poorly characterized in clinical transplantation. Thus, total B cell depletion treatments should be avoided and novel approaches should be considered that manipulate the different B cell subsets. This article provides an overview of the current knowledge on the link between Breg cells and grafts, and reports a number of data advising Breg cells as a new target for future therapeutic approaches.